A Qualitative Study of Data Management Development for Hybrid Organisation Application - Noorhasyimah Ismail; Azlan Ab Rahman; Aina Mardziah Ahmad Rifa’i; Siti Munira Jamil; Nur Liyana Zakaria; Hanisah Abdul Rahman (International Journal of Interactive Mobile Technologies (iJIM), 2022)
A revolution of information technology through big data for data processing is greatly affecting organisations around the globe, specifically the education providers. Subsequently, there are increasing needs and demands for software, digitalisation, and processing power development for unlimited database development and applications. The study aims to determine how well-prepared UTMSPACE is in meeting the new data management planning requirement for developing the big data management application. This study is supplementary to the development of strategic management planning in digitalisation and data management. The study employs qualitative method for its exploratory and data processing application research. The findings will help to identify the weaknesses and strengths in preparing data management applications to achieve strategic management plan outcomes. The study suggests that the company must increase awareness on the importance of big-data management through data processing engines that provide a more organised and centralised data and information management. In addition, the results also share the type of data and information needed for prioritising the organisational strategies in implementing the lifelong learning programmes across different environments and sectors.